Friend or Foe: The Importance of Identifying Bacteria with Biochemical Tests - Schieferecke, Grace (Kansas State University. K-State Libraries, 2022)
Identifying bacteria by utilizing biochemical tests is important, as bacteria can have a great impact on humans. Some bacterial strains are helpful while others are harmful, and having the ability to precisely identify bacteria can be crucial in maintaining human health. Biochemical tests generally consist of both selective and differential medias. Selective media only allows particular organisms to grow on it, while differential media will produce differing results, like a change in color, with the growth of different species. In this report, two bacterial strains were identified by performing a Gram stain and a series of selective and differential tests. Using an expected results table, the strains were identified as _Enterococcus faecalis_, a probiotic, and _Proteus vulgaris_, a potentially pathogenic bacterium. Correctly identifying bacteria is important in determining further steps after discovering bacteria in area from the food industry to the medical field.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, grand prize
Keywords: Enterococus Faecalis; Proteus Vulgaris; Bacterial Identification; Bacterial Strain; Pathogenic Bacterium; Biochemical Test